O retrato em movimento das violações de direitos humanos nos jornais de Cascavel: sua inferência sobre a rebelião da Penitenciária Estadual de Cascavel em 24 de agosto 2014 - Jurumenha, Mary Andréa Alves (2017)
The objective of this work was to investigate the possible association between the events of August 24, 2014, at the State Penitentiary of Cascavel-PEC , which is the target of interpretations lacking in scientificity, both by the local press and by the national press and official data from the Penitentiary Department National. Official information has not yet been released, and the only consensus so far is that conditions set by law have not been met. From this perspective, we pass on the importance of this work linked to the prison institution, since it is the State that selects sentences and protects the grieving. To that end, it has a multidisciplinary team in prisons and other welfare agencies, for which the maintenance and guarantee of human rights is a key element in resolving conflicts and verifying the suppression of human dignity. We revere the traditional works that deal with Human Rights, but our study will be focused largely on Brazilian works, written by authors who know our reality and dedicate themselves to discussing the theme. The purpose of this study is to understand, understand and analyze the rebellion that occurred in Cascavel, indicating whether or not there was a violation of the human rights of detainees and those directly associated with them. In order to complete this verification, we use the local press data and the National Report of Penitentiary Information-INFOPEN . These sources allow us to recognize that there is a historical social segregation, which disrupts collective living, having as its last expression the prison system.